2020
DOI: 10.1001/jamacardio.2020.2159
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Recipients of Heart Transplant With Coronavirus Disease 2019

Abstract: IMPORTANCERecipients of heart transplant (HT) may be at increased risk of adverse outcomes attributable to infection with coronavirus disease 2019 (COVID-19) because of multiple comorbidities and clinically significant immunosuppression.OBJECTIVE To describe the characteristics, treatment, and outcomes of recipients of HT with COVID-19. DESIGN, SETTING, AND PARTICIPANTSThis case series from a single large academic heart transplant program in New York, New York, incorporates data from between March 1, 2020, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
217
5
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(256 citation statements)
references
References 15 publications
23
217
5
11
Order By: Relevance
“…9−13 Ren et al 14 reported a low rate of suspected cases of SARS-CoV-2 infection and no death in a series of 87 heart transplant patients; however, none had a laboratory confirmation of infection. Latif et al 12 reported a case fatality rate of 25% in a series of 28 heart-transplanted patients with a confirmed diagnosis of COVID-19.…”
mentioning
confidence: 99%
“…9−13 Ren et al 14 reported a low rate of suspected cases of SARS-CoV-2 infection and no death in a series of 87 heart transplant patients; however, none had a laboratory confirmation of infection. Latif et al 12 reported a case fatality rate of 25% in a series of 28 heart-transplanted patients with a confirmed diagnosis of COVID-19.…”
mentioning
confidence: 99%
“…Review of the clinical courses showed that most of the transplant patients were managed successfully without progression of the disease. However, some other studies revealed that transplant recipients experienced more severe COVID-19 pneumonia and a more difficult recovery than their infected family members and those in the general population [21][22][23]. In a case series of 12 patients with a history of kidney transplantation in Iran [24], the fatality rate reached 67%, and the author concluded the majority of the clinical features in deceased cases were similar to those from other adult studies for the general population.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Latif et al described a single-center case series of 28 HTR with con rmed diagnosis of COVID-19 in the United states. The median time from HT was 8.6 years, and the case fatality rate was 25% [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the current context of coronavirus disease 2019 (COVID- 19), the management of patients with endstage heart failure on the transplant waiting-list is challenging. To date, only few case reports or small case series of COVID-19 in heart transplant recipients (HTR) have been described in China, Spain, Germany, and the United States, with mainly HTR who were remote from transplant [1][2][3][4][5][6][7]. Herein, we report on two HTR who developed and ultimately died from severe COVID-19, a few days after their urgent transplant procedure (TP).…”
Section: Introductionmentioning
confidence: 94%